2016
DOI: 10.3390/coatings6010009
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Functionality of Cells Cultured on Conducting and Semi-Conducting Surfaces Modified with Self-Assembled Monolayers (SAMs)

Abstract: Abstract:Bioengineering of dermal and epidermal cells on surface modified substrates is an active area of research. The cytotoxicity, maintenance of cell phenotype and long-term functionality of human dermal fibroblast (HDF) cells on conducting indium tin oxide (ITO) and semi-conducting, silicon (Si) and gallium arsenide (GaAs), surfaces modified with self-assembled monolayers (SAMs) containing amino (-NH 2 ) and methyl (-CH 3 ) end groups have been investigated. Contact angle measurements and infrared spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Silanes are generally known to form self-assembled monolayers when deposited onto a glass surface and thus offer a simple way to change the surface properties through display of specific functional groups . It was found that APTES preserves the viability and proliferation of human dermal fibroblast and does not deteriorate the potency of mesenchymal stem cells . To validate this surface treatment, we flow nonviable cells through a device with a ridge angle of 15° with and without the triethoxysilane treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Silanes are generally known to form self-assembled monolayers when deposited onto a glass surface and thus offer a simple way to change the surface properties through display of specific functional groups . It was found that APTES preserves the viability and proliferation of human dermal fibroblast and does not deteriorate the potency of mesenchymal stem cells . To validate this surface treatment, we flow nonviable cells through a device with a ridge angle of 15° with and without the triethoxysilane treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several novel applications of ITO have emerged. Aithal et al [31] observed maintenance of cell phenotype and long-term functionality of human dermal fibroblast (HDF) cells on ITO modified by self-assembled monolayers (SAMs). This important advance is significant for the future development of bioengineered skins.…”
Section: Introductionmentioning
confidence: 99%